Performance evaluation of nano-enhanced phase change materials for thermal energy storage: An experimental study - Mehmet Onur Karaağaç (Case Studies in Thermal Engineering)
In rapidly developing economies, the increasing energy demand and fossil fuel consumption have made the need for renewable energy sources and efficient thermal energy storage (TES) solutions more urgent than ever. This study focuses on enhancing the thermal energy storage capabilities of paraffin-based phase change materials (PCMs) by incorporating Al2O3, MgO, and CuO nanoparticles. The evaluation of nano-enhanced PCMs focused on their melting temperatures, thermal storage capacities, thermal conductivities, and charge/discharge times. The experimental results revealed significant changes in the thermal properties of the nano-enhanced PCMs compared to pure paraffin. The melting temperature was raised by 2 °C due to Al2O3 nanoparticles, whereas CuO and MgO nanoparticles decreased it by 1.7 °C and 1.8 °C, respectively. Compared to pure paraffin, Al2O3-PW, MgO-PW, and CuO-PW exhibited improvements of 13 %, 39 %, and 48 % in thermal conductivities, respectively. CuO-doped paraffin showed an 11.8 % decrease in discharge time, suggesting its suitability for rapid heat transfer applications like defrosting systems or thermal management in electronics. On the other hand, paraffin doped with MgO showed a minimal 2.24 % reduction in discharge time, indicating its effectiveness in applications requiring heat retention, particularly for improved thermal insulation in building materials. The results highlighted the potential of nano-enhanced PCMs in energy storage and construction is underlined, offering a sustainable approach to improving energy efficiency in various sectors.